Solve the following question
Attachments:
![](https://hi-static.z-dn.net/files/d62/f4a6e6b846d7222ba5c8382aaf003fed.jpg)
Answers
Answered by
1
3+√2/3-√2 =a+b√2
Rationalisong the denominator
Multiply both numerator and denominator by 3+√2
(3+√2)(3+√2)
--------------------
(3-√2)(3+√2)
= (9+2+6√2)
----------------
9-2
= 11+6√2
---------
7
ie;
11+6√2
----------- = a + b √2
7
Equating,
a=11/7
b=6/7
Hope that helped.
^_^
Rationalisong the denominator
Multiply both numerator and denominator by 3+√2
(3+√2)(3+√2)
--------------------
(3-√2)(3+√2)
= (9+2+6√2)
----------------
9-2
= 11+6√2
---------
7
ie;
11+6√2
----------- = a + b √2
7
Equating,
a=11/7
b=6/7
Hope that helped.
^_^
Similar questions
Math,
9 months ago
Social Sciences,
9 months ago
Math,
1 year ago
English,
1 year ago
Hindi,
1 year ago